STRATEGI PELAYANAN PUBLIK YANG BERORIENTASI KEPADA PENGGUNA LAYANAN PUBLIK - A.M. Yadisar (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Classic problems in public services such as complicated procedures and low user satisfaction require a strategy update that is oriented to the needs of the community. This study aims to formulate a strategy for developing user-based public services at the Population and Civil Registration Office of Sintang Regency through a qualitative approach. Using in-depth interviews and document studies, this study found that bureaucratic reform and organizational culture have a significant influence on service quality. Implementation of the values of service ethics, accountability, and public responsibility are key factors. Public service development strategies will be effective if they are designed integratively-involving organizational structure, technology, human resources, and institutional values together. Service strategies cannot stand alone without the support of cross-field coordination, simplification of regulations, and data-based evaluation. The conclusion confirms that the success of public service development lies in changing the work culture of the apparatus that focuses on user satisfaction and procedural efficiency. It is expected that service providers can develop a roadmap, increase human resource capacity, strengthen participatory evaluation systems, develop user-friendly digital applications, simplify service structures and procedures adaptively, instill a work culture of public services, increase public digital literacy, ensure the sustainability of service innovation.